Avaliação do estresse, ansiedade e comportamento associados ao tratamento odontológico infantil sob sedação - Rodrigues, Heloisa de Sousa Gomes (2016)
Paediatric dental treatment may stress children and their parents influencing the child behaviour and the maternal dental anxiety. It is important to understand those behavioural and physiological alterations to aid using of adequate sedatives techniques during paediatric dental procedure. The aim of this study was to evaluate the stress of children and their mothers during the paediatric dental treatment using different sedation protocols. Also, the maternal dental anxiety, the child’s behaviour and age and its associations were evaluated. This observational study is a secondary analysis of two randomised controlled clinical trials. Children aged 2-6 years old received one tooth restoration under moderate sedation according to the groups: [A] 18 children received oral midazolam (1.0 mg/kg) and [B] 18 children received placebo in a crossover design [Clinical Trials database (NCT01795222)]; [C] 14 children received oral midazolam (0.5 mg/kg) and oral ketamine (3.0 mg/kg) plus sevoflurane inhalation (0.3% - 0.4%) and [D] 13 children had oral midazolam (0.5 mg/kg) and oral ketamine (3.0 mg/kg) plus oxygen inhalation in a parallel design (NCT02284204). The sessions were video recorded for evaluation of child behaviour using OSUBRS scale (Ohio State University Behavioural Rating Scale) and mothers answered the Brazilian version of Dental Anxiety Scale (DAS). The saliva samples were collected on children and on their mothers at 4 moments: waking up (T0), upon arrival at Dental School (T1), 25 minutes after the local anaesthesia injection on child (T2) and 25 minutes after the end of procedure (T3). Salivary cortisol was measured using an immunoassay kit (ELISA). As the data presented non normal distribution (Shapiro Wilk, p>0,05), Kruskal-Wallis and Mann-Whitney tests were used for non paired comparisons and Mann-Whitney for associations among the variables. For paired comparisons, Friedman and Wilcoxon tests were used (p<0,05). The increase of cortisol levels from T1 to T2 (reactivity to stressful stimulus – local anaesthesia) was higher in children of group [B] [median (interquartile)] – [0.53 (0.60)] following by groups [D] – [0.21 (0.35)], [C] – [0.11 (0.49)] and [A] – [0.02 (0.59)] (p=0.02). The decrease of cortisol levels from T2 to T3 (regulation to stress) was higher in children of group [B] – [0.08 (0.29)] following by groups [A] [-0.02 (0.40)], [C] – [-0.18 (0.41)] and [D] – [-0.19 (0.8)] (p=0.02). Majority of mothers were not stressed during their child’s local anaesthesia injection (67.9%) and presented low/moderate anxiety (69.6%), while 25.0% of them presented high/severe anxiety (DAS scale). Mothers who reacted to stress (increasing of cortisol at least 10% from T1 to T2) had higher cortisol levels at the moments T2 [0.15 (0.48)] and T3 [0.16 (0.50)] compared to T1 [0.09 (0.17)] (p<0.01 and p<0.006, respectively). On the other hand, mothers who did not react to stress had higher cortisol levels at the moments: T1 [0.36 (0.18)] compared to T2 [0.16 (0.18)] (p<0.01) and T3 [0.10 (0.12)] (p<0.01) and T2 compared to T3 (p=0.01). There was no statistically significant association between maternal stress (salivary cortisol levels) with child behaviour (p=0.56), child’s age (p=0.48) and maternal dental anxiety (DAS) (p=0.69). The findings of this study allow to conclude that sedation protocol using oral ketamine caused higher liberation of salivary cortisol at the moments of local anaesthesia and at the end of procedure (higher reactivity and lower regulation) indicating a prolonged response to physiological stress in children, which was not observed during the use of oral midazolam. Although, there was any maternal dental anxiety most of mothers were not stressed during the dental treatment under sedation of their children. Also, maternal dental anxiety, child’s age and child behaviour did not influence the maternal stress.